Barbados : Financial System Stability Assessment; Update, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents Barbados's Financial System Stability Assessment Update as part of the Financial Sector Assessment Program Update. The domestic banking sector appears sound and profitable and continues to dominate the financial system. The financial system has benefited from the strong economic expansion, which has boosted credit demand while contributing to a steady improvement in banks' asset quality. Capital adequacy for locally incorporated banks remains above the minimum required, and profits remain at healthy levels.